Implementasi Kebijakan Penanganan Anak Jalanan di Kota Yogyakarta - Pratiwinegara, Ayu Isrovani; Sundarso, Sundarso; Hidayat, Zainal (Journal of Public Policy and Management Review, 2015)
Policy implementation of street children handling is one of the effort made by the government to remove the children lived in the street by fulfill their rights. Policy implementor are Social Service, Labour and Transmigration of Yogyakarta and the Association of Social Worker Yogyakarta. The purposes of this research are to analyze the process of policy implementation of street children handling and factors that support and hinder policy implementation of street children handling in Yogyakarta city. The effectiveness of the policy implementation process viewed from 4 factors: appropriateness of the policy, the accuracy of the executor, the target accuracy, and precision of the environment. For enabling and inhibiting factors using the theory of Van Meter and Van Horn are standard and policy objectives, resources, communication between organizations and implementing activities, the characteristics of the implementing agency, social, political, and economic environment and disposition implementor. This study used a qualitative approach with descriptive type of research, because research aimed to illustrate how the process of policy implementation of street children handling performed deeply by the facts. Analysis of this research were field observation, interview, and literature study. Then doing reduction data, data presentation, and drawing conclusions based on the analysis and presentation of data. The results of this research wasn’t able to solve the existing problems of street children yet, but able to reduced the number of street children. The inhibiting factors were funds, private role, social and economic environment of Yogyakarta city.